1996
DOI: 10.1074/jbc.271.45.28206
|View full text |Cite
|
Sign up to set email alerts
|

Different Pathways of Postreceptor Desensitization following Chronic Insulin Treatment and in Cells Overexpressing Constitutively Active Insulin Receptors

Abstract: We have reported previously that substitution of the transmembrane domain of the insulin receptor with that of the erbB-2 oncogene (IR erbV3 E ) results in constitutive activation of the insulin receptor kinase. Compared to NIH3T3 cells overexpressing wild-type insulin receptors (IR wt ), cells overexpressing IR erbV3 E displayed a decrease in IRS-1 protein content by 55%, but basal tyrosine phosphorylation of IRS-1 was increased. This resulted in an increased association of IRS-1 with the p85 subunit of phosp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0
2

Year Published

2000
2000
2009
2009

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 37 publications
0
15
0
2
Order By: Relevance
“…The amino-truncated variant form of EGFR, denoted EGFRvIII, is constitutively active and is found in human brain, breast, lung and ovarian tumors (Voldborg et al, 1997). Downstream of this receptor, the Ras-MAPK pathway was downregulated (Moscatello et al, 1996), and PI3-kinase and c-Jun N-terminal kinase were chronically activated (Inoue et al, 1996;Moscatello et al, 1998) in NIH3T3 cells. Constitutive activation of the insulin receptor in NIH3T3 cells induced constitutive activation of PI3-kinase and unresponsiveness of MAPK activation by insulin, EGF, and platelet-derived growth factor (Antonyak et al, 1998).…”
Section: Discussionmentioning
confidence: 99%
“…The amino-truncated variant form of EGFR, denoted EGFRvIII, is constitutively active and is found in human brain, breast, lung and ovarian tumors (Voldborg et al, 1997). Downstream of this receptor, the Ras-MAPK pathway was downregulated (Moscatello et al, 1996), and PI3-kinase and c-Jun N-terminal kinase were chronically activated (Inoue et al, 1996;Moscatello et al, 1998) in NIH3T3 cells. Constitutive activation of the insulin receptor in NIH3T3 cells induced constitutive activation of PI3-kinase and unresponsiveness of MAPK activation by insulin, EGF, and platelet-derived growth factor (Antonyak et al, 1998).…”
Section: Discussionmentioning
confidence: 99%
“…MAPK assay. MAPK activity was measured with an immune complex assay as previously described (10). The incorporation of radioactivity to myelin basic protein was analyzed with the Bio-Imaging Analyzer BAS-2000 (Fuji Photo Film) after separating with SDS-PA G E .…”
Section: Methodsmentioning
confidence: 99%
“…We measured the half-life of IRS-1 in the presence and in the absence of IGF-I by [ 35 S]methionine- Increased insulin concentrations result in decreased IRS-1 expression. It has previously been shown that insulin at high (micromolar) concentrations causes a decrease in IRS-1 expression (23,47). We therefore tested the ability of insulin, at low (nanomolar) and at high (micromolar) concentrations, to decrease IRS-1 expression in MCF-7 cells (Fig.…”
Section: Igf-i Stimulation Decreases Irs-1 Expression In a Time-andmentioning
confidence: 99%
“…Conversely, decreased IRS-1 expression, achieved by antiestrogen treatment, inhibited IGF-I signaling through IRS-1. In a number of cell systems it has been shown that high concentrations of insulin can cause posttranscriptional downregulation of IRS-1 expression (23,47), a potential mechanism being proteolytic degradation of IRS-1 protein by the calpain pathway (54). IRS-1 phosphorylation is regulated by receptor tyrosine kinases, protein tyrosine phosphatases, and serine/threonine kinases.…”
mentioning
confidence: 99%